Basic Japanese Grammar - Breiler, Everett (Tuttle, 2011)
This book teaches you all the grammar need to speak and understand simple spokenn Japanese. Covering only what is essenstial, it proficiency in the language and to begin to communicate natrrally with Japanese speakers immediately